Sinonasal and Skull Base Malignancies - Saba, Nabil F.; Lin, Derrick T.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book reviews the standard surgical, radiotherapeutic, and systemic management of sinonasal and skull base tumors. It provides up-to-date information on epidemiology, diagnostic modalities, molecular biology, staging, treatment complications, principles of supportive care, and current controversies. Sinonasal and skull base tumors display histologic and anatomic heterogeneity, as well as wide variation in clinical behavior. Accordingly, they pose significant diagnostic and treatment challenges. A multidisciplinary approach offers the best chance of a successful outcome. In addition to documenting in detail the currently accepted management approaches, this book sheds light on various promising novel therapeutic strategies. Sinonasal and Skull Base Malignancies is an invaluable reference for all specialists involved in treating these tumors, including otolaryngologists, head and neck surgeons, reconstructive surgeons, medical and radiation oncologists, neuroradiologists, specialized head and neck pathologists, prosthodontists, and speech and swallow therapists.
The Etiology and Epidemiology of Sinonasal Malignancies -- Radiology and Diagnostic Approaches to Sinonasal Malignancies and Skull Base Tumors -- The Pathology of Common Sinonasal and Skull Base Malignancies -- Open Approaches to Sinonasal Tumors -- Reconstruction and Rehabilitation after Surgical Ablation of the Paranasal Sinuses -- Endoscopic Resection of Sinonasal Tumors -- Endoscopic Reconstruction of the Skull Base -- Radiation Therapy for Sinonasal and Skull Base Tumors -- Theroleofsystemictherapyandtargetedapproaches for the treatment of sinonasal malignancies,- Complications of Surgical Management of Skull Base and Sinonasal Malignancies -- Supportive care for patients with sinonasal and skull base tumors -- Rare Sinonasal and Skull Base Tumors.
Keywords: Internal medicine; Otorhinolaryngology; Radiology; Internal Medicine; Otorhinolaryngology; Radiology; Paranasal Sinus Neoplasms; Skull Base Neoplasms